Elevated self‐esteem 12 months following a 10‐day developmental voyage. Issue 9 (21st August 2013) - Hunter, John A.; Hayhurst, Jill; Kafka, Sarah; Boyes, Mike; Ruffman, Ted; O'Brien, Kerry; Stringer, Maurice
Abstract The following article examined elevated self‐esteem as a function of a 10‐day developmental voyage. Two studies were conducted. Study 1 demonstrated that participants who completed the voyage experienced elevated self‐esteem. Study 2 replicated and extended these results insofar as it revealed that (a) elevated self‐esteem was maintained 12 months following the voyage; and (b) increasing levels of perceived self‐efficacy and belonging (as assessed on the last day of the voyage), but not social support, each made a unique contribution to these effects. Together, these findings provide converging evidence to suggest that a 10‐day developmental voyage upon the Spirit of New Zealand promotes elevated self‐esteem that is maintained over time, and that perceived self‐efficacy and belonging contribute to this outcome.